2009
DOI: 10.1007/s11606-009-0992-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physicians Treat Somatization

Abstract: BACKGROUND:We hypothesized that somatizing patients managed by primary care physicians (PCP) would improve with a relationship-based intervention. METHODS:We randomized 30 adults with medically unexplained symptoms to treatment or usual care. Four PCPs were trained to intervene with cognitivebehavioral, pharmacological, and patient-centered management and deployed the intervention with seven scheduled visits over 12 months. Outcomes obtained at baseline and 12 months were: Mental component summary (MCS), the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 19 publications
0
16
0
3
Order By: Relevance
“…Smith and his colleagues [46] in the United States have particularly advanced the field in developing a multidimensional intervention based on three principles from the literature which seemed to be effective: collaborative/stepped care, the use of cognitive-behavioural therapy skills and the centrality of the patient-provider relationship in working with patients with medically unexplained symptoms [46]. This model, which has similarities to that described by van der Feltz-Cornelis who combined aspects of reattribution training, cognitive-behavioural skills and consultation liaison [28] has recently been piloted successfully with moderatelarge effect sizes reported [47] and in parallel qualitative research [48] the authors have reported:…”
Section: Comparison With Other Approaches In the Literaturementioning
confidence: 99%
“…Smith and his colleagues [46] in the United States have particularly advanced the field in developing a multidimensional intervention based on three principles from the literature which seemed to be effective: collaborative/stepped care, the use of cognitive-behavioural therapy skills and the centrality of the patient-provider relationship in working with patients with medically unexplained symptoms [46]. This model, which has similarities to that described by van der Feltz-Cornelis who combined aspects of reattribution training, cognitive-behavioural skills and consultation liaison [28] has recently been piloted successfully with moderatelarge effect sizes reported [47] and in parallel qualitative research [48] the authors have reported:…”
Section: Comparison With Other Approaches In the Literaturementioning
confidence: 99%
“…Twenty studies met the inclusion criteria for the present meta-analysis [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. We identified 850 records through database searching and screening of reference lists of previous systematic reviews and meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…27 Studies suggest physicians tend to default toward prescribing medications with dubious benefits to patients with MUS, even when those patients are not asking for pharmacological treatment. 28 Research indicates that medication, 29,30 cognitive-behavioral therapy, 31 and patient-centered management 32,33 may help relieve MUS, though there are contradictory findings. 34,35 It seems reasonable in a biopsychosociospiritual 9,10 model for physicians to explore all options with the patient, but our results demonstrate that physicians' religious characteristics and specialty will influence which option a physician prefers, and how they interpret the cause of MUS.…”
Section: Discussionmentioning
confidence: 99%